(untitled) (Gestión y Gerencia, 2020)
The TECOVEN C.A company, is dedicated to the refrigeration equipment manufacturing, makes a maximum of 10 of these daily. From the FIM productivity manual, the areas of human resources, supplies and maintenance were selected, since they are the main causes of production delays. The study includes a diagnostic stage of the company’s situation regarding the level of compliance of the FIM productivity manual, followed by a determination of the causes that generate non-compliance, then an improvement plan is drawn up to increase the level of compliance and finally, the impact of the proposed improvements is evaluated. After the evaluations carried out, it was obtained that, if the improvement proposals were implemented, 100% compliance would be obtained for human resources, 66.66% for supplies and 82.76% for maintenance, where daily production is expected to increase to 64 refrigeration units. It is concluded that the delays incidence in the mentioned areas is reduced and the planned production goal is reached, allowing the company to operate efficiently in the present and to adapt to the continuous changes in the future.